The position of man in the infosphere. Towards a ‘new’ philosophical anthropology? - Ridolfi, Giorgio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2025)
Luciano Floridi has repeatedly pointed out that the development of the modern infosphere brings with it the appearance of a new type of human being. Hence, according to the Italian scholar, the need to develop a new philosophical anthropology. After analysing Floridi’s position, the essay seeks to understand whether the classical philosophical anthropology can be in any way useful in describing the evolution of the contemporary world, mainly in its informational meanings. Accordingly, Floridi’s doctrines will be compared with those of the three masters of twentieth-century anthropology ‒ Max Scheler, Helmuth Plessner, Arnold Gehlen ‒ in order to find anticipations and possible refutations.